Dilema Legalitas dan Kriminalisasi Penambang Rakyat: Perjuangan Aliansi Tambang Rakyat Bangka dalam Menuntut Kepastian Hukum di Wilayah Pertambangan Rakyat - Yopi Ardiansyah; Meydilah Ayu Nafisah; Vera Ayu Lestari; Ade Saputra Dinata (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Bangka Belitung Islands Province as the largest tin producer faces legality dilemmas and criminalization of artisanal miners due to permit centralization through Law Number 3 of 2020. This study aims to analyze the impact of centralization on artisanal miners' legal access, criminalization practices under Article 158 of the Mineral and Coal Law, and the form of Bangka Artisanal Miners Alliance (ATRB) struggle demanding legal certainty. The research employs qualitative case study approach with data collection techniques through literature study and document analysis of regulations, court decisions, and media reports. Findings show centralization narrows legal access causing slow and bureaucratic process for Artisanal Mining Area (WPR) designation and Artisanal Mining Permit (IPR) issuance. Criminalization practices more frequently affect small-scale miners major actors, creating injustice perceptions and worsening socio-economic conditions of mining households. ATRB emerges as a social movement demanding legal recognition through accelerated WPR and IPR plus economic redistribution through fair tin trade governance. Non-transparent royalty management reaching Rp1.7 trillion worsens community vulnerability. This research contributes to social movement and natural resource politics studies by emphasizing the importance of participatory legalization and governance reform to reduce social conflict.